Causality of anti-Helicobacter pylori IgG levels on myocardial infarction and potential pathogenesis: a Mendelian randomization study - Wang, Qiubo; Liu, Yingbo; Xu, Zhenxing; Wang, Zhimiao; Xue, Mei; Li, Xinran; Wang, Ye (Frontiers in Microbiology, 2023)
Background: Previous observational studies have shown that a potential relationship between anti-Helicobacter pylori (H. pylori) IgG levels and Myocardial Infarction (MI). Nevertheless, the evidence for the causal inferences remains disputable. To further clarify the relationship between anti-H. Pylori IgG levels and MI and explore its pathogenesis, we conducted a Mendelian randomization (MR) analysis.Method: In this study, we used two-sample Mendelian Randomization (MR) to assess the causality of anti-H. pylori IgG levels on MI and potential pathogenesis, 12 single nucleotide polymorphisms (SNPs) related to anti-H. pylori IgG levels were obtained from the European Bioinformatics Institute (EBI). Summary data from a large-scale GWAS meta-analysis of MI was utilized as the outcome dataset. Summary data of mediators was obtained from the FinnGen database, the UK Biobank, the EBI database, MRC-IEU database, the International Consortium of Blood Pressure, the Consortium of Within family GWAS. Inverse variance weighted (IVW) analysis under the fixed effect model was identified as our main method. To ensure the reliability of the findings, many sensitivity analyses were performed.Results: Our study revealed that increases of anti-H. pylori IgG levels were significantly related to an increased risk of MI (OR, 1.104; 95% CI,1.042-1.169; p = 7.084×10 −4 ) and decreases in HDL cholesterol levels (β, -0.016; 95% CI, -0.026 –0.006; p = 2.02×10 −3 ). In addition, there was no heterogeneity or pleiotropy in our findings.Conclusion: This two-sample MR analysis revealed the causality of anti-H. pylori IgG levels on MI, which might be explained by lower HDL cholesterol levels. Further research is needed to clarify the results.